2019
DOI: 10.7717/peerj.7854
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of RUNX1 in clear cell renal cell carcinoma predicts poor prognosis

Abstract: Background Runt-related transcription factor 1 (RUNX1) was previously reported to play a dual role in promoting or suppressing tumorigenesis in various malignancies. A public dataset from The Cancer Genome Atlas (TCGA) was used to evaluate the role of RUNX1 in clear cell renal cell carcinoma (ccRCC). Methods The Wilcoxon signed-rank test was used to compare the expression of RUNX1 in ccRCC tissues and normal tissues. The Wilcoxon signed-ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 22 publications
2
6
0
Order By: Relevance
“…Kaplan-Meier survival analysis of the ccRCC patients with RUNX1 mRNA upregulation shows that they have a statistically significant decrease in survival compared to the unaltered cohort (Log-rank P=0.0008, RUNX1 Unaltered median=76.98 months, RUNX1 mRNA upregulation median=36.21 months) ( Supplementary Fig1c). This is in line with a recent report interrogating the TCGA dataset (35). Furthermore, data obtained using the pan-cancer RNA-seq KM plotter (36) tool analysing clinical survival data from 530 ccRCC patients also show that high RUNX1 expression correlates with poorer overall survival (P<0.0001), ( Supplementary Fig1d).…”
Section: Runx1 Is Expressed In Human Ccrcc and Correlates With Poor Ssupporting
confidence: 90%
“…Kaplan-Meier survival analysis of the ccRCC patients with RUNX1 mRNA upregulation shows that they have a statistically significant decrease in survival compared to the unaltered cohort (Log-rank P=0.0008, RUNX1 Unaltered median=76.98 months, RUNX1 mRNA upregulation median=36.21 months) ( Supplementary Fig1c). This is in line with a recent report interrogating the TCGA dataset (35). Furthermore, data obtained using the pan-cancer RNA-seq KM plotter (36) tool analysing clinical survival data from 530 ccRCC patients also show that high RUNX1 expression correlates with poorer overall survival (P<0.0001), ( Supplementary Fig1d).…”
Section: Runx1 Is Expressed In Human Ccrcc and Correlates With Poor Ssupporting
confidence: 90%
“…For example, RUNX1 was inhibited by miR-106a-5p, thereby enhancing osteosarcoma tumorigenesis ( 29 ). RUNX1 was observed to be increased in renal cell carcinoma and was associated with poor prognosis ( 30 ). Keita et al identified RUNX1 as a tumor promotor in ovarian cancer and skin cancer ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Increasingly, it has been implicated in cancers of ovary [30] , prostate [31] and stomach [32] , which was associated with either gain or loss of RUNX1 function. Recently, Yang et al revealed that higher RUNX1 expression may be associated with poorer survival in RCC [33] ; this was later confirmed by Rooney et al who utilized a genetically engineered mouse (GEM) model [18] .…”
Section: Discussionmentioning
confidence: 90%